Attitudes of Religious Tolerance in Junior High School Students - Evi Susilawati; Nimim Nimim; Agung Suharyanto; Darmayasa Darmayasa (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to analyze the level of religious tolerance of junior high school students. This study uses a quantitative method with a descriptive approach. The respondents amounted to 31 students. Data was collected through a questionnaire with 11 statements. Then the data were analyzed by means and percentage analysis. The results of the study show that tolerance is viewed from the aspect of peace, respect for differences and individuals, and awareness is in the very good or very tolerant categories. This is indicated by the average score for the three aspects located in the interval 3.75 - 5.00. This data indicates that students' religious tolerance is still well maintained so as to create harmonious relationships among students.